The Natural History of Metabolic Comorbidities in Turner Syndrome from Childhood to Early Adulthood: Comparison between 45,X Monosomy and Other Karyotypes - Lebenthal, Yael; Levy, Sigal; Sofrin-Drucker, Efrat; Nagelberg, Nessia; Weintrob, Naomi; Shalitin, Shlomit; de Vries, Liat; Tenenbaum, Ariel; Phillip, Moshe; Lazar, Liora (Frontiers in Endocrinology, 2018)
Objective: Patients with Turner syndrome (TS) are at increased risk for metabolic disorders. We aimed to delineate the occurrence and evolution of metabolic co-morbidities in TS patients and to determine whether these differ in 45,X monosomy and other karyotypes. Methods: A longitudinal and cross-sectional retrospective cohort study was conducted in a tertiary pediatric endocrine unit during 1980-2016. Ninety-eight TS patients, 30 with 45,X monosomy were followed from childhood to early adulthood. Outcome measures included weight status, blood pressure (BP), glucose metabolism and lipid profile. Results: Longitudinal analysis showed a significant change in BMI percentiles over time (F(3,115)=4.8, P=.003). Age was associated with evolution of elevated BP (systolic BP: OR=0.91, P=.003; diastolic BP: OR=0.93, P=.023), impaired glucose metabolism (HbA1c: OR=1.08, P=.029; impaired glucose tolerance: OR=1.12, P=.029) and abnormal lipid profile (cholesterol: OR=1.06, P=.01; LDL-cholesterol: OR=1.07, P=.041; HDL-cholesterol: OR=1.07, P=.033). The occurrence of metabolic co-morbidities was similar in 45,X monosomy and other karyotypes. Coexistence of multiple metabolic co-morbidities was significantly higher in 45,X monosomy [F(1,72)=4.81, P=.032]. BMI percentiles were positively correlated with metabolic co-morbidities (occurrence and number) in each patient (r=0.35, P=.002 and r=0.383, P=.001, respectively). Conclusions: Our longitudinal study provides unique insights into the evolution of weight gain and metabolic disorders from childhood to early adulthood in TS patients. Since overweight and increasing age aggravate the risk for metabolic co-morbidities, careful surveillance is warranted to prevent and control obesity already from childhood. The more prominent clustering of metabolic co-morbidities in 45,X monosomy underscores the importance of a more vigorous intervention in this group.